KOMPOSISI KEPEMILIKAN SAHAM, LIKUIDITAS DAN ABNORMAL RETURN DI SEKITAR PENGUMUMAN STOCK SPLIT PADA PERUSAHAAN PUBLIK DI BURSA EFEK JAKARTA - Najmudin, Najmudin; Indiyastuti, Nurhayati (Performance, 2007)
This paper aims to examine: (1) The effect of stock splits on share ownership composition, liquidity, and return for splitting firms; (2) Linkages among those three variables and ownership composition prior to the split as a conditioning variable; and (3) Relationship between liquidity change and ownership composition change as anintervening variable. The sample observed in this study was the firm listed at Jakarta Stock Exchange during period 1995 - 2000 and splitting the stock during January 1997 – December 1998, this sample was selected based on purposive sampling method. The research method used is event study, i.e. research methodology designed to measure the impact of an event of interest on stock returns.The analysis yields three main results: (1) The stock split does not change the ownership composition and the level of liquidity. (2) The effect of stock split on ownership composition and liquidity is conditional on the level of institutional ownership prior to the split. Firms with high institutional ownership prior to the split experience decrease in institutional ownership, while firms with low institutional ownership prior to the split do not change. Changes in liquidity are negatively affected by the level of institutional ownership prior to the split and positively affected by changes in institutional ownership proportion. (3) There are positive abnormal returns following the stock split. The abnormal returns are not related to the level of institutional ownership prior to the split.